Bairro Planalto, Natal-RN: agentes, usos e conflitos - Silva, João Henrique Gomes da (2014)
This research has the goal to analyze the urban setting of the Planalto neighborhood, in Natal /RN, seeking to unravel the processes, agents and contradictions associated with the production of the space. The choice of neighborhood is justified by the observation that changes in its urban setting have been growing in speedy way. We highlight the performance of the housing market, in partnership with the state, and the construction of condominiums and buildings closed by the housing program Minha Casa, Minha Vida. This has favored the reproduction of a new " urban reality in the neighborhood, setting an urban standard that differs from the original morphology, seen as peripheral within the urban dynamics of the city. The research is a qualitative study, through documents, interviews with stakeholders, and photographic documentation. In this perspective , we seek to understand the current phase (2000s) the production of space in the neighborhood process through the development of the housing market , as an extension of the urban development in central zone of Natal/RN, analyzing the performance of agents and their producers the "new " uses redefining the "old ". Thus, it can be seen that there is in the neighborhood, urban reality in a pluralistic constitution, from the existence of different social classes inhabiting the same space. On this way, the city is produced from the appropriation of space by different social classes, although due to the economic condition of each of them